Apoyo social y empatía como predictores de satisfacción con la vida en estudiantes universitarios brasileños - Huanca López, Sanny Raquel (2023)
The objective of this paper was to study if social support and empathy predict life satisfaction in Brazilian university students. Through a non-probabilistic sampling for convenience, the voluntary participation of 374 Brazilian university students over 18 years of age from public and private universities was sought. The questionnaires applied were the Zimet Social Support scale, the Jolliffe and Farrington Basic Empathy scale (BES) and the SWLS Life Satisfaction Scale by Diener. The results showed a relationship between the variables Social Support and Empathy with a result of 0.217 (p<0.01), relationship between Social Support and Satisfaction with life is 0.415 (p<0.01). Likewise, a relationship was found between empathy in its Affective dimension -0.103 (p<0.05), and in its Cognitive dimension 0.104 (p<0.05) with satisfaction with life. The regression analysis showed that 18.9% of the variability of Satisfaction with life is explained by the variables Social Support and Empathy. The result of the t test shows that the dimensions of friends and important people of the social support variable and the affective dimension of the empathy variable are significant and has a significant effect for the criterion variable, which is Satisfaction with life. It is concluded that social support and empathy are predictors of life satisfaction with Brazilian university students. This indicates the importance of developing a social support intervention program to improve life satisfaction in students.